Evolution of the Financial Market. Cryptocurrency - A. Ya. Zaporozhan (Управленческое консультирование)
The article is devoted to the causes of the origin, the consequences of the functioning of the crypto currency and the prospect of restructuring the modern financial system on the basis of blocking technology. The article shows that the crypto currency emerged as an evolutionary stage in the development of the world payment system, that the modern financial system is developing in a dead-end direction, that the use of crypto currency and its derivatives in practice can destroy the world payment system and world financial market from within. It is suggested that, based on the technology of the block, a modern financial system can be restructured.